2011
DOI: 10.1348/014466510x511637
|View full text |Cite
|
Sign up to set email alerts
|

Trauma rehabilitation for war-affected persons in northern Uganda: A pilot evaluation of the EMPOWER programme

Abstract: OBJECTIVES. This study evaluated the impact of a culturally sensitive cognitive behaviour therapy (CBT)-based intervention (the EMPOWER programme) for war-affected persons in northern Uganda. DESIGN. The study conducted a pilot evaluation with a convenience sample of participants from internally displaced persons (IDPs) camps (i.e., a treatment camp and waitlist control camp). This was done to avoid treatment effects spreading from the intervention to control conditions. METHODS. A total of 202 participants (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…Other nations where internal displacement has occurred within the context of enduring armed conflicts include Uganda [6, 62, 66], Ethiopia [57], Sudan [58, 59, 70, 72, 73, 79, 81], and Sri Lanka [71, 74]. Prior to displacement, future IDPs witness nearby armed conflict and other acts of violence [6, 67•, 68••, 6977, 71, 7478].…”
Section: Discussionmentioning
confidence: 99%
“…Other nations where internal displacement has occurred within the context of enduring armed conflicts include Uganda [6, 62, 66], Ethiopia [57], Sudan [58, 59, 70, 72, 73, 79, 81], and Sri Lanka [71, 74]. Prior to displacement, future IDPs witness nearby armed conflict and other acts of violence [6, 67•, 68••, 6977, 71, 7478].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on depression, anxiety, and PTSD reported reductions and an overall improvement in mental function among intervention groups compared to control groups. 37,50,52,58 Improvements were often not observable at the early stages of the interventions, for example within the first three months. However, even minimal engagement within the intervention proved beneficial compared to no intervention at all.…”
Section: Treatment and Essential Drugs Interventionsmentioning
confidence: 99%
“…A culturally sensitive CBT-based group intervention trialed in Uganda with 202 internally displaced persons (aged 15–56 years) was the EMPOWER program (Sonderegger, 2006; Sonderegger et al, 2011). The program was developed to help war-affected persons overcome their traumatic experiences through teaching emotional resiliency and reconciliation.…”
Section: Introductionmentioning
confidence: 99%